Fihrist-i nasḵẖ-i qalmī ʻArabī, Fārsī, va Urdū : Subḥān Allāh Oriyanṭal Lāʼibrerī, Muslim Yūnivarsiṭī, ʻAlīgaṛh - Ḥusain, Sayyid Kāmil (Lāʼibrerī Kameṭī, Muslim Yūnīvarsīṭī, ʻAlīgaṛh, 1930)
Catalog of Arabic, Persian, and Urdu manuscripts preserved in the Aligarh Muslim University Library.